Great myths of intimate relationships dating, sex, and marriage - Johnson, Matthew D. 1978- (Great myths of psychology, 2016)
"Great Myths of Intimate Relationships provides a captivating, pithy introduction to the subject that challenges and demystifies the many fabrications and stereotypes surrounding relationships, attraction, sex, love, internet dating, and heartbreak. The book thoroughly interrogates the current research on topics such as attraction, sex, love, internet dating, and heartbreak Takes an argument driven approach to the study of intimate relationships, encouraging critical engagement with the subject Part of The Great Myths series, it's written in a style that is compelling and succinct, making it ideal for general readers and undergraduates "-- Provided by publisher.